Design of Application Planning Field Officer Elections - Febi Kadarianto; Vivine Nurcahyawati; Sri Suhandiah (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
PT Superintending Company of Indonesia (SUCOFINDO) surabaya move in the service sector inspection and audit, testing and analysis, certification service, training service, and consultation. The company has some parts namely the administration, financial, operation, human resources, marketing, sales and support operation. The operating part is a part a main in the service for customers, the role of this part to support operating by digging resources from the personnel and put him on the operational in accordance with qualifications.                     Management and data processing the choice of officers field recently applied PT SUCOFINDO  done manually and less objective. It was considered objective is an election officers who is not based on their competence the elections without seeing lifetimes and track record of activity the officers. Because curriculum vitae and track record wasn’t archived  well in addition to compare between the officers one with other officers needed accurate and time because it’s should be flip through the curriculum vitae tree and track record. Factor the choice of officers the field namely curriculum vitae tree and track record, the status of the presence of officers, and calculation manday ( salary ) per day.                Their final task is research that yields planning application selection officers to assist with the management the choice of officers , based on the results of the trial and evaluation research.